Use of monoclonal antibodies as a therapeutic option for breast cancer treatment: A review - Alvarado-Arce, Aldeír (2025)
[Objective] The objective of the research was to compile/analyze the information available about the use of monoclonal antibodies as a therapy for breast cancer. [Methodology] A bibliographic review was conducted using databases and journal publications addressing monoclonal antibodies as a treatment for cancer. The review focused on current data reflecting the scope and limitations of monoclonal therapy in different types of cancer. Additionally, a strategy was proposed to mitigate the negative side effects associated with the treatment in patients of cancer. [Results] Hybridoma cells target receptors responsible for the proliferation of cancer cells, such as HER2 in breast cancer, inhibiting their multiplication and facilitating the immune system’s ability to attack damaged cells through lymphocytes. Despite being a promising treatment, it has associated negative side effects. Therefore, an immunosuppression treatment plan is proposed to counteract these effects without compromising the therapy’s effectiveness. In Costa Rica, research including monoclonal antibodies as a potential cancer treatment should be promoted to improve patients’ quality of life. [Conclusions] The use of monoclonal antibodies as a treatment for breast cancer has shown positive results in patients, as it is a highly specific technique. However, many obstacles remain in its application, creating gaps that hinder research aimed at improving patient prognosis.